Resistance And Adaptation Of Traditional Islamic Education Towards Modernization At Al Manshuriyah Islamic Boarding School - Chafidzotur Rofi’ah Alfaddi; Ehwanudin; Nurul Aisyah (Journal of Research in Islamic Education, 2026)
Al Manshuriyah Islamic Boarding School, as a traditional Islamic educational institution, plays a strategic role in maintaining the transmission of Islamic values. This boarding school is known for its unique integration of classical religious curricula with modern teaching methods, such as the use of information technology for teaching yellow books and Arabic, as well as additional skills programs that support global competency. The modernization process, characterized by technological developments and curriculum changes, requires Islamic boarding schools to adapt without losing their traditional identity. This study aims to analyze the forms of resistance and adaptation of traditional Islamic education to modernization at Al Manshuriyah Islamic Boarding School. This study is a field study with a descriptive approach. Data collection techniques were carried out through observation, in-depth interviews with boarding school administrators, ustaz, and students, as well as documentation studies. The results show that resistance is demonstrated through efforts to maintain the yellow book teaching system, the pattern of kiai-santri relationships, and the preservation of the boarding school's religious traditions. Meanwhile, adaptation is realized through the integration of the formal curriculum, the use of technology in learning, and the development of students' skills according to the needs of the times. These findings confirm that Islamic boarding schools do not completely reject modernization, but rather select and recontextualize it to align with Islamic values ​​and the pesantren's character. This research is expected to provide theoretical contributions to the study of Islamic education and serve as a practical reference for pesantren administrators in managing change wisely and sustainably.